TINGKAT KESESUAIAN ISI IKLAN PROMOSI AKADEMIK BINA SARANA INFORMATIKA DI YOUTUBE PERIODE 2010-2016 BERDASARKAN ETIKA PARIWARA INDONESIA - Robbikal Muntaha Meliala (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: This research is aimed to know how far academic promotion advertisement of Bina SaranaInformatika in Youtube Period 2010-2016 inline to Ethics of Indonesia Advertisement 2014 seemed from article1.2 language term, article 1.16 testimony term, article 1.20 humiliate message to the other competitor, article1.21 imitated message and article 2.19 Education Institution & Job Vacancy. 12 research samples of promotionadvertisement were founded by the author with census sampling technique. Techniques of data collecting aretest of categories by coders, literature review, and documentation. Research methodology that author used iscontent analysis of quantitative approached. From discussion of research result, can be concluded: reliabilityvalue of test categories with minimum value (77,8%). Modus (91,67%) has been founded in variable 1 and 3,they are appropriateness article 1.2.1 and 1.20, but article 1.2.2 the usage of superlative language was stillfounded with violation (41,67%). Appropriateness article 1.21 was founded with violation (16.67%) andappropriateness article 2.19.1 was founded with violation (41,67%). Meanwhile, the biggest percentageviolation was founded in variable 2 about appropriateness article 1.16 (91,67%) in category 2 and 3 abouthyperbola testimony from consumers and lack of consumer’s identity when they were speak up to the audiences. Keywords: Advertisement, Ethics of Indonesia Advertisement